Rancang Bangun Alat Pemotong Krecek Kerupuk dengan Pendekatan Ergonomi pada UD Dua Saudara di Desa Bodor Kabupaten Nganjuk - Bagus Yulianto, Dwiki; Puspanantasri Putri, Erni (SURYA TEKNIKA, 2024)
Abstract UD Dua Saudara is a company engaged in the food industry, namely krecek crackers, the krecek cracker industry is owned by Mr. Lukman, located in Bodor Village, Pace District, Nganjuk Regency. The production process of making krecek crackers at UD Dua Saudara experiences obstacles, especially during the process of cutting krecek crackers, which is the main obstacle in the krecek cracker production process. To carry out a fast and efficient cutting process, there are several obstacles such as tools and work techniques that are still traditional, less efficient, and ergonomic, so that during the cutting process it can take longer and the results are not optimal. There is also the result of cutting in an average day - 136 Kg, to be more efficient, a tool redesign is needed that can overcome these problems. And I hope that later the tool can make the cutting process more efficient, ergonomic and can also increase capacity. From these problems, I designed a krecek cutting tool with an ergonomic approach. The results of data collection and processing obtained dimensional results for the tool with the following: to determine the width of the frame using the 95th percentile, namely 45cm, to determine the height of the tool with the 95th percentile, namely 60cm, to determine the Grip handle using the 95th percentile, namely 5cm.